Condensation Resistance Evaluation of a Double-sliding Window System for Apartment Buildings. (2016) - Park, Sihyun; Koo, So Young; Lim, Jae-Han; Seong, Yoon-Bok; Song, Seung-Yeong
Abstract: In a cold climate such as Korea, the condensation risk is high for window systems. Condensation can lead to mold or mildew problems, thereby causing discomfort for building occupants. To evaluate the risk of condensation for residential apartment buildings, the most commonly used double-sliding window system with double glazing on a four-track polyvinyl chloride (PVC) frame was examined as a reference model. A variety of different frame profile options has been proposed as alternatives to existing window systems. The condensation risk from the reference model was compared to that of the alternatives using two-dimensional steady-state heat transfer simulations. The temperature difference ratio (TDR) was calculated for each case using the inside surface temperature determined at the evaluation locations by the simulation results. Then, these TDRs were compared to determine the most improved alternative.